Efektivitas Model Pembelajaran Berbasis Masalah pada Pembelajaran Gardu Induk di Sekolah Menengah Kejuruan - Khatrin Maharani; Sukardi Sukardi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
This study aims to determine the effectiveness of the problem-based learning model in TJTL class XII substation subjects at SMK Negeri Padang. Student learning outcomes are still low caused by factors that seem monotonous learning methods. Therefore, it is necessary to do research using a problem-based learning model. This study uses a type of pre-experimental research. The design of this research is The One-Shot Case Study. According to Sumadi (2003: 100)